PENGARUH APLIKASI PADLET BERBASIS VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SDN 1 SYAMTALIRA BAYU - Intan Wahyuni; Misrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low ability to understand students' mathematical concepts, one of the causes of which is the lack of use of interesting and varied learning media. The purpose of this study was to determine the effect of using the Padlet application based on learning videos on the ability to understand mathematical concepts of fifth grade students of SDN 1 Syamtalira Bayu. This study used a quantitative approach with a quasi-experimental design. The sample consisted of 41 students divided into two groups: the experimental class using the Padlet application, and the control class using conventional learning methods. The instruments used were pretest and posttest. The results showed that the average posttest score of students in the experimental class was higher (84.5) than the control class (71.90). However, based on the t-test statistical test, a significance value of 0.425 (> 0.05) was obtained, indicating that the difference was not statistically significant. This means that although on average there was an increase in learning outcomes, there was no statistically significant effect between the use of the Padlet application based on learning videos and the improvement of students' mathematical concept understanding abilities. This study shows that the Padlet application can be a fun and interesting alternative media for students in understanding mathematical concepts. The novelty of this study lies in the use of video-based Padlet which is rarely applied at the elementary school level, especially in mathematics learning.